Low-intensity Politicide: Territorialized Extermination of the Partido Revolucionario de los Trabajadores (PRT) in the Colombian Caribbean, 1991-2005 (2022)
Objective/Context: The following article analyzes the politicide of the Partido Revolucionario de los Trabajadores (PRT) after signing the peace agreement between this guerrilla group and the Colombian government in 1991. It shows how studies on genocides and politicides fall into an error that we call “quantity bias” in this article since they only consider large-scale exterminations of political groups, leaving out the analysis of exterminations carried out in a more selective and localized manner. Based on a critical review of the specialized literature, the study constructs a typology of different forms of political assassinations, deriving from it the concept of low-intensity politicide, proposed as the most appropriate category of analysis for the case study of the PRT. Methodology: A case study based on a documentary review and semi-structured interviews with former members of the PRT, FARC-EP, and AUC. Conclusions: Among the main findings, it is evident how low-intensity politicides, such as the one that occurred with the PRT, are characterized by being executed mainly through individual selective violence, having a local/regional geographic scope and their main perpetrators tending to be paramilitary groups in alliance with local elites and State agents. Originality: The theoretical contribution of the study consists of proposing a new category, such as low-intensity politicide, for the analysis of other cases of political extermination. It is also the first academic research focused on the extermination of the PRT. © 2022 Universidad de los Andes, Bogota Colombia. All rights reserved.